Impact of Sexual Attitude and Marital Intimacy on Sexual Satisfaction in Pregnant Couples: An Application of the Actor-Partner Interdependence Model - Hee Eun Kim; Jung Hee Yeo (Korean Society of Women Health Nursing, 2017)
PURPOSE: The purpose of this study was to investigate actor and partner effects of sexual attitude and marital intimacy on sexual satisfaction in pregnant couples. METHODS: Data were collected from 176 pairs of the pregnant couples visiting for prenatal care at hospitals from June 18 to September 24, 2016. The collected data were analyzed by paired t-test and Pearson's correlation coefficients using SPSS 18.0 and interdependent effect (Actor-Partner Interdependence Model analysis) through AMOS 18.0. RESULTS: The sexual attitude and marital intimacy of the pregnant woman did not have a partner effect on the sexual satisfaction of her husband, respectively (β=.12, p=.141), (β=.01, p=.938). The sexual attitude of the husband had a partner effect on the sexual satisfaction of the pregnant woman (β=.13, p=.021), but the marital intimacy of the husband did not show a partner effect (β=.07, p=.202). CONCLUSION: Study suggests that the sexual attitude and marital intimacy of pregnant couples should be considered as factors when developing an intervention to improve sexual satisfaction in couples. Moreover, pregnant couples should participate in intervention together because the sexual satisfaction has conceptual view of interdependence in two-person relationships.